SEVERAL PROBLEMS WITH PLANNING OF TRANSPORT PROVISION OF EVACUATION (Perner's Contacts, 2014)
Civil protection presents a set of activities, where on the one of significant position is a transport provision of evacuation of persons, animals or objects. Transport provision of evacuation can be understood as a set of activities, related to planning, preparation and implementation of transport of persons, animals and objects outside the zone of danger. To ensure an effective planning of transport provision of evacuation, there must be assess a number of important factors. These factors are discussed in the article.
Keywords: transport; evacuation; planning; provision